Nailfold capillaroscopy in systemic sclerosis – state of the art: The evolving knowledge about capillaroscopic abnormalities in systemic sclerosis. Issue 3 (October 2019) - Lambova, Sevdalina Nikolova; Müller-Ladner, Ulf
Capillaroscopy is a unique method for morphological evaluation of the nailfold capillaries that plays a crucial role for early diagnosis of systemic sclerosis. The first description of the pathological capillaroscopic changes in systemic sclerosis was made by Brown and O'Leary in 1925. Several decades later they have been validated and accepted as a diagnostic criterion in the current 2013 EULAR/ACR classification criteria. This article summarizes the evolving knowledge about the use of nailfold capillaroscopy in systemic sclerosis. Initially, Maricq et al. suggested two major categories of capillaroscopic findings in systemic sclerosis – an 'active'and 'slow' capillaroscopic pattern. Their description and terminology suggested a correlation between capillaroscopic changes and disease activity and progression. In the later classification of Cutolo et al., three phases were defined, i.e. 'early', 'active' and 'late' that reflect the time-related evolution of the capillaroscopic changes suggesting their association with disease duration. Current knowledge about the microvascular changes in systemic sclerosis supports both associations with disease activity and disease duration. The general opinion about the association of capillaroscopic findings with clinical involvement and disease activity in systemic sclerosis is not uniform. This is supposedly because the phase changes of systemic sclerosis–related microangiopathy are almost a universal feature in scleroderma and are not specific for a certain type of an accompaning clinical manifestation. Thus, the speed of progression of microvascular alterations might be a decisive criterion, and in cases of rapid dynamics of capillaroscopic findings, it could be considered as an indicator of disease activity. Interestingly, vascular 'recovery' has been observed after treatment with immunosuppressive drugs, haematopoietic stem cell transplantation, and the endothelin receptor antagonist – bosentan. The evolving knowledge about nailfold capillaroscopy in systemic sclerosis will further spread its application from a mainly diagnostic tool to an established, reliable method for evaluation of disease activity, prognosis and therapeutic response.